A REINSTATEMENT, RECIRCUMSCRIPTION AND REVISION OF THE GENUS DONELLA (SAPOTACEAE) - Mackinder, B.; Harris, D. J.; Gautier, L. (Edinburgh Journal of Botany, 2016)
The genus Donella Pierre ex Baill. is here reinstated and Austrogambeya Aubrév. is, for the first time, placed in synonymy based on the findings of recent combined molecular and morphological studies. Seventeen species are recognised, two of which, Donella ranirisonii L.Gaut. & Mackinder and D. humbertii Capuron ex Mackinder & L.Gaut., from Madagascar, are described here for the first time. The flowers of Donella ambrensis and D. delphinensis are described here for the first time, as are the fruits of D. guereliana. Two keys, to the species of Madagascar and tropical Africa, respectively, are presented. Ten species are endemic to Madagascar, six species are endemic to tropical Africa and one, Donella lanceolata, occurs from Madagascar to the Solomon Islands. For each species, the accepted name with synonymy is given, followed by a morphological description. Geographical range and details of habitat are provided, with taxonomic and/or nomenclatural notes as appropriate. Distribution maps are presented for all species, and preliminary conservation assessments are made. Five species qualify for a category of Threat, and three further species are assessed as Near Threatened. An index to species and a list of exsiccatae are included.
Keywords: Angiosperms; Austrogambeya; Chrysophylloideae; Chrysophyllum; conservation status; Gambeya; new species; palaeotropics; taxonomic study